Method of manufacturing a wear layer

CN117396451BActive Publication Date: 2026-10-20SAFRAN AIRCRAFT ENGINES SAS +3
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202280038026.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-05-25
Filing Date
2022-05-16
Publication Date
2026-10-20
Estimated Expiration
2042-05-16

AI Technical Summary

Technical Problem

该解决方案提供了非常好的结果;然而,这种解决方案会产生相对较高的孔隙率,介于30%和50%之间,因此某些要求特别高的应用需要更高的耐侵蚀性

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117396451B_ABST
    Figure CN117396451B_ABST
Patent Text Reader

Abstract

The invention relates to a method of manufacturing a wear-resistant layer and a substrate coated with the layer, comprising the steps of: preparing a powder composition (30) comprising at least ceramic particles and an inorganic filler having a layered crystal structure, the volume content of the inorganic filler in the powder composition being between 1% and 75%; compressing the powder composition (30); and sintering the thus compressed powder composition (30) to obtain a wear-resistant layer (12).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for manufacturing a wear-resistant layer and a substrate coated with the layer.

[0002] This wear-resistant layer is particularly useful for equipping rotating machine rings to ensure a seal, for example, at the tips of rotating blades. It is especially suitable for turbine rings in the aerospace field, and particularly for use in aircraft turbojet engines. Background Technology

[0003] Currently, wear-resistant layers are used in gas turbines to minimize functional clearances between rotating and stationary components, thereby minimizing leakage. For high-pressure turbine applications, wear-resistant seals are deposited on annular sectors attached to the housing. During contact between the turbine blades and the wear-resistant material, the latter must wear preferentially, thus maintaining the engine's aerodynamic performance.

[0004] However, it is also necessary to protect the substrate from temperatures up to 1600°C and from airflow erosion under high temperature and pressure. With this in mind, a refractory metal-based ceramic coating is typically formed on the stationary portion of the annular sector via thermal spraying to create a thermal barrier protective coating. However, the resulting coating does not exhibit very high wear resistance, which can lead to wear at the blade tips during operation, resulting in complex and costly repairs.

[0005] To enhance the wear resistance of thermal barriers, various solutions have been envisioned in the prior art. These solutions include incorporating pore-forming agents to increase the porosity of the barrier. However, these solutions are not entirely satisfactory because they significantly reduce the corrosion resistance of the coating, thereby shortening the service life of both the barrier and the underlying substrate.

[0006] Another solution described in application FR3044945 uses spark plasma sintering (SPS) to generate abrasion-resistant coatings with gradient properties, particularly including lower porosity at the coating edges for better resistance to erosion. However, while providing good results, this solution requires special preparation of the substrate.

[0007] Another solution described in application FR3082765 uses yttrium-stabilized zirconia powder with various shape factors. This solution provides very good results; however, it results in a relatively high porosity, between 30% and 50%, thus requiring higher corrosion resistance for certain particularly demanding applications.

[0008] Therefore, there is a need to provide a method for manufacturing a wear-resistant layer that has both good wear resistance and good corrosion resistance. Summary of the Invention

[0009] The present invention relates to a method for manufacturing a wear-resistant layer, comprising the following steps: preparing a powder composition, the powder composition comprising at least ceramic particles and an inorganic filler having a layered crystal structure, wherein the volume content of the inorganic filler in the powder composition is between 1% and 75%; compressing the powder composition and sintering the compressed powder composition to obtain a wear-resistant layer.

[0010] Using the powder composition defined above and the pressure sintering technique, it is advantageously possible to obtain layers with good wear resistance and good corrosion resistance. Furthermore, the inventors have observed that, at the same porosity, or even in some cases, with greater porosity, wear-resistant layers formed by pressure sintering exhibit better corrosion resistance than layers formed by plasma spraying.

[0011] Furthermore, inorganic fillers allow for the filling of some of the large pores created in the ceramic matrix at the end of the sintering process. This results in lower porosity and thus better corrosion resistance.

[0012] However, this lower porosity does not necessarily translate into a loss of wear resistance. In fact, due to its layered crystalline structure, the inorganic filler exhibits solid lubricating properties, creating a weak interface between the ceramic matrix and the inorganic filler, thereby promoting crack propagation and mechanically weakening the ceramic matrix. Therefore, the resulting composite material, despite its lower porosity, possesses toughness and microhardness values ​​comparable to those of conventional ceramic wear-resistant layers.

[0013] In some embodiments, at least 50% by weight, preferably at least 80% by weight, more preferably at least 95% by weight, of the ceramic particles have a shape factor greater than or equal to 3, and more preferably greater than or equal to 5. However, it is preferably less than or equal to 30. In particular, the ceramic particles can be ceramic fibers. Such particles result in an oriented microstructure, promoting the propagation of dislocations and cracks between the filler and the matrix. They also result in two types of porosity: mesopores within the fibers and macropores between the fibers and the inorganic filler.

[0014] Unless otherwise stated, the average shape factor expressed in terms of quantity corresponds to the average value of the following ratio R calculated for each particle in a given particle group, where R represents the ratio [maximum particle size] / [maximum lateral particle size].

[0015] In some embodiments, at least 50% of, preferably at least 80% of, and more preferably at least 95% of the ceramic particles have a shape factor of less than or equal to 1.5, and more preferably less than or equal to 1.1. Under such conditions, the inorganic filler and the particles of the ceramic matrix form agglomerates of different sizes.

[0016] In some embodiments, at least 50% of, preferably at least 80% of, and more preferably at least 95% of the ceramic particles have a size between 10 and 100 μm. The maximum particle size is taken into consideration here.

[0017] In some embodiments, the ceramic particles are yttrium oxide-stabilized zirconia particles. This material is typically abbreviated as (YSZ).

[0018] In some embodiments, the inorganic filler has chemical and structural temperature resistance greater than 1300°C. This enables the inorganic filler to resist the prevalent high temperatures, particularly in turbines of turbine engines.

[0019] In some embodiments, the coefficient of thermal expansion of the inorganic filler is close to that of the ceramic particles, within ±20%, preferably within ±15%. This reduces the risk of differential expansion observed within the wear-resistant layer, which can lead to microcracks and significantly reduce its corrosion resistance.

[0020] In some embodiments, the thermal conductivity of the inorganic filler is less than 10 W·m-1 K, preferably less than 5 W·m-1 K. Therefore, the inorganic filler helps to protect the substrate of the thermally protective wear layer from the effects of the prevalent high temperatures, especially in turbines of turbine engines.

[0021] In some embodiments, the microhardness of the inorganic filler is less than that of the ceramic particles, preferably at least 20% less, more preferably at least 50% less. Specifically, the microhardness of the ceramic particles can be less than 5 GPa. Therefore, the inorganic filler has low mechanical strength, which contributes to the good wear resistance of the wear-resistant layer.

[0022] In some embodiments, the Young's modulus of the inorganic filler is less than that of the ceramic particles, preferably at least 20% less. Specifically, the Young's modulus of the inorganic filler can be less than 180 GPa. Therefore, the inorganic filler has low mechanical strength, which contributes to the good wear resistance of the wear-resistant layer.

[0023] In some embodiments, the toughness of the inorganic filler is less than that of the ceramic particles, preferably at least 20% less, more preferably at least 80% less. Specifically, the toughness of the inorganic filler can be less than 2 MPa.m. 1 / 2 .

[0024] In some embodiments, the inorganic filler is lanthanum oxide, preferably LaPO4 or La2Zr2O7. These compounds meet all the required mechanical and thermal standards.

[0025] In some embodiments, at least 50 vol%, preferably at least 80 vol% and more preferably at least 95 vol% of the inorganic filler is in the dehydrated phase. In particular, it can be the monazite phase. The effect of this dehydrated phase is improved solid lubrication and dislocation properties.

[0026] In some embodiments, the method includes a thermal pretreatment step for the inorganic filler, performed at a temperature between 800 and 1600°C, preferably between 800 and 1400°C, more preferably between 900 and 1200°C, even more preferably between 1000 and 1150°C, and still more preferably between 1050 and 1150°C. This thermal pretreatment step allows control over the crystallinity of the inorganic filler and its transformation to a dehydrated phase. Since the crystallinity of the phase affects the sintering behavior of the inorganic filler, this step allows control over the mechanical properties of the filler and its cohesion with the ceramic matrix. In particular, this step allows for the adjustment of the microstructure of the inorganic filler to allow good compatibility between the sintering temperature of the filler and the sintering temperature of the matrix, thereby achieving uniform consolidation of the component, resulting in good wear resistance.

[0027] In some embodiments, the thermal pretreatment step of the inorganic filler lasts for 30 to 120 minutes, preferably 60 to 120 minutes.

[0028] In some embodiments, the volume content of inorganic filler in the powder composition is 10% to 50%, preferably 25% to 35%. In fact, the inventors have determined that such a content achieves an excellent trade-off between abrasion resistance and corrosion resistance.

[0029] In some embodiments, the powder composition consists essentially of the ceramic particles and the inorganic filler.

[0030] In some embodiments, the method includes the step of mixing the powder composition. Such a mixing step can control the dispersion of the inorganic filler within the ceramic matrix. It also affects the shape factor of the ceramic particles. Therefore, the mixture can be controlled to obtain an agglomerated mixture or even a more homogeneous mixture by selection.

[0031] In some embodiments, the mixing step is performed by dry mixing, preferably using a three-dimensional dynamic mixer.

[0032] In some embodiments, the three-dimensional dynamic mixer includes mixing beads with a mass ratio of the mixing beads to the powder composition between 0:1 and 1:1. A mass ratio close to 1:1, for example greater than 0.8:1, makes it possible to obtain a more homogeneous mixture, while a mass ratio close to 0:1, for example less than 0.2:1, makes it possible to obtain a more agglomerated mixture.

[0033] In some embodiments, the mixing step lasts from 5 minutes to 4 hours, preferably 1 to 2 hours.

[0034] In some embodiments, the mixing step is performed by liquid mixing.

[0035] In some embodiments, the mixing step is performed by synthesizing inorganic fillers directly in a suspension of ceramic particles. This makes it possible to obtain ceramic particles coated with inorganic fillers, resulting in different and equally interesting distributions of the fillers in the microstructure after sintering.

[0036] In some embodiments, the sintering step is performed by discharge plasma sintering. This sintering technique allows for better control of sintering parameters, thereby better control of the porosity obtained at the end of sintering.

[0037] In some embodiments, the pressure, temperature and duration of sintering applied during the sintering process are selected to obtain a volumetric porosity of the wear-resistant layer between 0.1% and 50%, preferably between 25% and 35%, which is less than the porosity typically observed in conventional ceramic wear-resistant layers.

[0038] In some embodiments, during the sintering step, the powder composition is subjected to a uniaxial pressure of 25 to 100 MPa, preferably 80 to 100 MPa or 40 to 60 MPa.

[0039] In some embodiments, the applied temperature during the sintering step is between 900°C and 1200°C, preferably between 1100°C and 1200°C. Preferably, such a temperature is applied once pressure is applied.

[0040] In some embodiments, the duration of the sintering step is between 1 and 30 minutes.

[0041] This disclosure also relates to a method for manufacturing a substrate coated with a wear-resistant layer, the substrate being a turbine engine component, wherein the wear-resistant layer is formed on the substrate by performing the method according to any one of the foregoing embodiments, and a powder composition is deposited on the surface of the substrate.

[0042] This alternative involves a situation where a powder composition is first deposited on a substrate, and then a wear-resistant layer is formed directly on the substrate by sintering the deposited powder composition under pressure.

[0043] This disclosure also relates to a method for manufacturing a substrate coated with a wear-resistant layer, the substrate being a turbine engine component, comprising the steps of: manufacturing the wear-resistant layer by performing the method according to any one of the foregoing embodiments, depositing the thus manufactured wear-resistant layer on the surface of the substrate, and bonding the thus deposited wear-resistant layer to the surface of the substrate.

[0044] This alternative involves a situation where a wear-resistant layer is first formed, then the wear-resistant layer is deposited on a substrate and then bonded to the substrate.

[0045] In some embodiments, the substrate is metallic or made of a ceramic matrix composite material.

[0046] In some embodiments, the substrate is a turbine or compressor annular sector.

[0047] In this disclosure, the terms “axial,” “radial,” “tangential,” “internal,” “external,” and their derivatives are defined relative to the main axis of the turbine engine. The term “axial plane” refers to a plane passing through the main axis of the turbine engine, and the term “radial plane” refers to a plane perpendicular to the main axis; finally, the terms “upstream” and “downstream” are defined according to the airflow in the turbine engine.

[0048] The above features and advantages, as well as other features and advantages, will become apparent from the following detailed description of exemplary embodiments of the proposed method. This detailed description refers to the accompanying drawings. Attached Figure Description

[0049] The accompanying drawings are schematic and are primarily intended to illustrate the principles of this disclosure.

[0050] In these accompanying figures, from one figure to another, the same elements (or parts of elements) are identified by the same reference numerals.

[0051] Figure 1 This is a cross-sectional view of a turbine engine.

[0052] Figure 2 This is a partial perspective view of an example of a substrate coated according to the method of this disclosure.

[0053] Figures 3A-3B Two consecutive steps of an exemplary method according to this disclosure are illustrated schematically.

[0054] Figure 4 This is the first scanning electron microscope image of ceramic particles that can be used in powder compositions.

[0055] Figure 5 This is a scanning electron microscope image of a second type of ceramic particle that can be used in powder compositions.

[0056] Figures 6A-6B It is a hydrated phase of inorganic filler that can be used in powder compositions. Figure 6A ) and dehydration phase ( Figure 6B Scanning electron micrographs of ).

[0057] Figure 7 The X-ray diffraction of this inorganic filler under various hydration states is shown.

[0058] Figures 8A-8C These are scanning electron micrographs of various powder compositions after mixing.

[0059] Figures 9A-9BThese are EDX (energy dispersive X-ray) images of two wear-resistant layers obtained after two different mixing steps.

[0060] Figure 10A and 10B Examples of temperature and compression pressure variations over time that can be used in the context of this disclosure are shown.

[0061] Figure 11 This is a scanning electron microscope image of the first wear-resistant layer.

[0062] Figure 12 This is another scanning electron micrograph of the first wear-resistant layer.

[0063] Figure 13A The Vickers microhardness of the wear-resistant layer as a function of the inorganic filler content is shown.

[0064] Figure 13B The toughness of the wear-resistant layer as a function of the inorganic filler content is shown.

[0065] Figure 14 The results of micro-scratch tests conducted on wear-resistant layers with different inorganic filler contents are shown.

[0066] Figure 15 This is a scanning electron microscope image of the second wear-resistant layer.

[0067] Figure 16A-16D The traces of wear resistance tests performed on various wear-resistant layers are shown.

[0068] Figure 17 The results of densification tests on two powder compositions treated at different temperatures are shown.

[0069] Figure 18A and 18B It shows the way Figure 17 The microstructure of the wear-resistant layer obtained for each powder composition tested.

[0070] Figure 19A and 19B It shows the way Figure 17 The wear resistance test marks on the wear-resistant layer obtained for each powder composition tested. Detailed Implementation

[0071] To make this disclosure more specific, examples of the method are described in detail below with reference to the accompanying drawings. It should be understood that the invention is not limited to these examples.

[0072] Figure 1A vertical cross-section is shown passing through the main axis A of the turbofan engine 1. It includes, from upstream to downstream, a fan 2, a low-pressure compressor 3, a high-pressure compressor 4, a combustion chamber 5, a high-pressure turbine 6, and a low-pressure turbine 7 in the airflow cycle.

[0073] The high-pressure turbine 6 includes multiple blades 6a that rotate with the rotor and a rectifier 6b mounted on the stator. The stator of the turbine 6 includes multiple stator rings disposed opposite to the moving blades 6a of the turbine 6. Figure 2 A stator ring is shown, which is divided into multiple sections, each section including a substrate 10 coated with a wear-resistant layer 12. In the event of radial intrusion of the rotor, the rotor blades 6a rub against the wear-resistant layer 12.

[0074] Reference Figure 3A and Figure 3B Examples of wear-resistant layer 12 are described. These... Figure 3A and 3B An implementation of an exemplary method according to the present invention is illustrated schematically.

[0075] The substrate 10 to be coated is placed in the cavity of the mold 20. Then, the powder composition 30 is deposited onto the surface S of the substrate 10. For example... Figure 3B As shown, the mold 20 is then closed. The contact surface of the mold cover 25 is applied to the powder composition 30 layer to compress it onto the substrate 10. The compression pressure applied to the powder composition 30 can be a uniaxial pressure. Therefore, the thickness of the powder composition 30 layer is reduced due to the compression between the substrate 10 and the cover 25. The powder composition 30 subjected to the compression pressure is then sintered. A discharge plasma sintering technique (“SPS”) can be performed to produce the wear-resistant layer 12. The wear-resistant layer 12 is obtained at the end of this sintering step.

[0076] In the example shown, the resulting wear-resistant layer 12 has a substantially uniform density. Alternatively, the wear-resistant layer can be formed to have a variable density, as described in application FR3044945.

[0077] An example is described with reference to the accompanying drawings, wherein the wear-resistant layer 12 is formed directly on the substrate 10 by a powder composition 30 pre-deposited on the substrate 10.

[0078] In an alternative not shown, the wear-resistant layer 12 can first be formed on a support member, different from the substrate, by performing a sintering method as described above under pressure. According to this alternative, the thus formed wear-resistant layer 12 is then separated from the support member to be positioned on the surface S of the substrate 10. The thus positioned wear-resistant layer 12 is then attached to the surface S of the substrate 10 to obtain a coated substrate. This connection can be made by brazing, sintering, or using added components (e.g., bolted connections).

[0079] The resulting wear-resistant layer 12 is particularly suitable for equipping high-pressure or low-pressure turbine rings or compressor rings, for example in the aerospace field, and more particularly in aircraft turbojet engines.

[0080] Various details relating to the substrate 10, the powder composition 30, and the operating parameters that can be applied during the method will now be described.

[0081] The substrate 10 can be a component for a turbine engine. The substrate 10 can be made of a metallic material, such as a superalloy. When the substrate 10 is made of a metallic material, it can be formed, for example, from one of the following materials: Alloy AMI, Alloy C263, or Alloy M509.

[0082] Alternatively, the substrate 10 may be made of CMC material. In this case, the substrate 10 may include woven fiber reinforcements formed of carbon fiber or silicon carbide fiber, which are densely packed by a ceramic matrix, such as silicon carbide. Specifically, a detailed example of the fabrication of a ring sector made of CMC is described in document US2012 / 0027572.

[0083] The substrate 10 may be coated with the wear-resistant layer 12, which is the anchoring layer to be coated (not shown). In the case of a metal substrate 10, an MCrAlY anchoring layer, such as a CoNiCrAlY anchoring layer, may be used. In the case of a substrate made of CMC, a mullite anchoring layer, for example, may be used.

[0084] For powder composition 30, it comprises ceramic particles and inorganic fillers.

[0085] The ceramic particles forming the powder are made of yttrium-stabilized zirconium oxide (YSZ). In some instances, these particles are nanospheres or quasi-spheres with an average shape factor of 0.9 to 1.1, preferably 1.0 to 1.1, for example, substantially equal to 1. These particles can be... Figure 4 You can see it in the small box.

[0086] These nanoceramic particles, in their non-agglomerated state, can have an average diameter of less than or equal to 70 nm, for example, between 30 nm and 70 nm. The diameter can be measured using a field emission gun scanning electron microscope (FEG-SEM). The average diameter corresponds to a numerical average.

[0087] An example of available nano-ceramic particles is the particle sold by Tosoh under the reference number Zirconia TZ6Y.

[0088] In other instances, these particles are fibrous: therefore, they have a variable shape factor, between 5 and 30, preferably between 15 and 25. Such particles... Figure 5 As shown.

[0089] The average diameter (or average width) of the fiber particles in the non-agglomerated state can be greater than or equal to 6 μm, for example, between 6 μm and 8 μm. The average length of the fiber particles can be greater than or equal to 125 μm, for example, between 125 μm and 215 μm.

[0090] The fiber particles that can be used in this disclosure may correspond to those described in patent application FR3082765.

[0091] The inorganic filler is in the form of lanthanum phosphate (LaPO4) powder. This powder is typically sold as a hydrated phase of lanthanum praseodymium phosphate (rhabdo-phane). This is especially true for the powder sold by Alfa Aesar under the reference number LPcom.

[0092] The commercial powder is then subjected to an initial heat treatment to dehydrate it and control its crystallinity, after which lanthanum phosphate transforms from the praseodymium phosphate phase to the monazite phase. This heat treatment is carried out at a temperature of at least 800°C and capable of reaching 1400°C, or even 1600°C. The duration of this treatment can range from 30 to 120 minutes.

[0093] therefore, Figure 6A and 6B The microstructures of lanthanum phosphate LaPO4 powder before and after the initial heat treatment are shown. Figure 7 The X-ray diffraction patterns are shown, highlighting the change in crystallinity of the inorganic filler over time. Curve 41 therefore corresponds to commercially available hydrated LaPO4 powder; curve 42 corresponds to the same powder after heat treatment at 800°C; and curve 43 corresponds to the same powder after heat treatment at 1000°C. The diffraction peaks narrow with increasing temperature, indicating a higher degree of crystallinity.

[0094] Then, by mixing the ceramic powder with the dehydrated inorganic powder, powder composition 30 is obtained. The volume content of inorganic powder in powder composition 30 can theoretically be between 1% and 75%; however, the best results are obtained when the volume content of inorganic powder is between 25% and 35%.

[0095] Then, using a three-dimensional dynamic mixer, such as the one sold by WAB under the brand name Turbula, the powder composition 30 undergoes a dry mixing step. The duration of this mixing step can be between 5 minutes and 4 hours.

[0096] Mixing beads can be added to the powder composition to promote mixing: when adding such beads, they can be added until a mixing ratio Rm is reached, corresponding to a mass ratio of [mixing beads]: [powder] equal to 1:1.

[0097] Figure 8AThe microstructure of a powder composition containing 75 vol% yttrium-stabilized zirconium oxide fibrous particles and 25 vol% lanthanum monazite after one hour of mixing at a 0:1 ratio is shown.

[0098] Figure 8B The microstructure of the same powder composition containing 75 vol% yttrium-stabilized zirconium oxide fibrous particles and 25 vol% lanthanum monazite after mixing for one hour at a 1:1 ratio is shown.

[0099] Figure 8C The microstructure of a powder composition containing 75 vol% yttrium oxide-stabilized zirconium oxide nanoparticles and 25 vol% lanthanum monazite after mixing for two hours at a 1:1 ratio is shown.

[0100] Therefore, it should be noted that Figure 8A An agglomerated mixture with inorganic filler aggregates within the fibrous ceramic particles is shown. In contrast, Figure 8B A more homogeneous mixture was observed.

[0101] Therefore, this agglomeration or uniform distribution is found in the sintered wear-resistant layer: this is in Figure 9A and 9B Clearly visible in the middle, Figure 9A and 9B It shows the results from... Figure 8A and 8B The EDX (Energy Dispersive X-ray) images of the wear-resistant layer obtained from the powder composition are shown. In fact, in these images, the dark areas represent the presence of zirconium oxide, and therefore the presence of the ceramic matrix from the ceramic particles, while the light areas represent the presence of lanthanum, and therefore the presence of the inorganic filler from the monazite particles.

[0102] Various details relating to the substrate 10 and the powder composition 30 will now be described. Details relating to the available wear-resistant layer 12 and the achievable operating conditions will now be described.

[0103] The volumetric porosity of the wear-resistant layer 12 can be between 5% and 50%, for example between 15% and 40%, for example between 25% and 35%, or even between 25% and 30%.

[0104] Temperature variations, sintering duration, and / or compressive pressure applied during sintering can alter the volumetric porosity of the resulting wear-resistant layer 12. Therefore, increasing the temperature, sintering duration, and / or compressive pressure can reduce the volumetric porosity of the wear-resistant layer 12.

[0105] Figures 10 and 11 show possible examples of how compression pressure and temperature change over time during the manufacture of the wear-resistant layer 12.

[0106] First, the assembly of substrate 10 and powder composition 30 is placed at a first temperature T1, for example, greater than or equal to 600°C. When the assembly reaches this first temperature T1, the compression pressure increases until a first time t1 is reached with P... c The value is a platform value corresponding to the compressive pressure that will be applied during the sintering of the powder composition 30.

[0107] The compressive pressure P applied to the powder composition 30 during sintering c The pressure can be between 25 and 100 MPa, for example, between 40 and 60 MPa, between 25 MPa and 50 MPa, or between 50 MPa and 100 MPa. The compressive pressure P is maintained throughout the sintering of the powder composition 30. c .

[0108] Starting from the first time t1, the temperature applied to the substrate 10 and the powder composition 30 is increased to the sintering temperature T. f The temperature reaches the sintering temperature T at the second time t2. f Then maintain that value. Sintering temperature T f The sintering temperature T depends on the properties of the powder composition 30 used. f It can be between 900℃ and 1200℃, for example, between 1100℃ and 1200℃.

[0109] Maintain sintering temperature T f and compression pressure P c The sintering process continues until the third time, t3. The sintering duration (t3-t2) can be greater than or equal to 1 minute, for example, between 1 and 30 minutes. Once sintering is complete, the compression pressure and temperature are gradually reduced, and then the substrate 10 coated with the wear-resistant layer 12 is recycled.

[0110] In the example shown, a first heating rate is applied between a first temperature T1 and a larger second temperature T2 reached at an intermediate time t1, and then at the second temperature T2 and the sintering temperature T f A second heating rate less than the first heating rate is applied between the two temperatures. For example, the first heating rate can be greater than or equal to 100°C / min, and the second heating rate can be less than or equal to 50°C / min. Again, for example, the second temperature T2 can be greater than or equal to 900°C. However, in other examples, the heating rate is between the first temperature T1 and the sintering temperature T... f The values ​​between them can be constant.

[0111] Figure 11The microstructure of a first example of a wear-resistant layer 12 obtained using this method is shown. In this first example, the powder composition comprises 75 vol% levels of yttrium oxide-stabilized zirconium oxide nanoparticles and 25 vol% levels of LaPO4 particles. The LaPO4 particles had previously undergone a heat treatment step at 800°C for 120 minutes. The powder composition was mixed by dry mixing for 120 minutes at a mixing ratio Rm of 1:1.

[0112] Sintering is performed via spark plasma sintering, with a compressive pressure P. c The pressure is 100 MPa, and the sintering temperature is T. f The temperature was 1150℃, and the duration was 10 minutes.

[0113] Figure 12 This is another photograph showing the microstructure of the fracture sites generated in the wear-resistant layer. The porosity of the obtained dense bulk material is between 2% and 10%, which is less than that of the composite material combining yttrium-stabilized zirconia fibrous particles and LaPO4 particles. The figure also shows strong debonding at the interface between the ceramic matrix and the inorganic filler. In particular, imprints can be seen in the magnified inset, which are formed by yttrium-stabilized zirconia nanoparticles left on the LaPO4 particles at the fracture surface.

[0114] Figure 13A , Figure 13B and Figure 14 The test results are then shown, which highlight the contribution of inorganic fillers in the YSZ matrix compared to the traditional YSZ wear-resistant layer.

[0115] therefore, Figure 13A and 13B Results of Vickers microhardness testing (according to standard ASTM E384 / ISO 6507) and single-edged notched bending (SENB) toughness testing are shown. In these tests, the wear-resistant layer was obtained from a powder composition combining yttrium-stabilized zirconia nanoparticles and LaPO4 filler treated at 800°C with varying filler concentrations.

[0116] It is noteworthy that both of these mechanical properties decrease linearly with increasing LaPO4 content. In particular, starting from 25% by volume of LaPO4, the microhardness and toughness values ​​reach levels comparable to those of conventional YSZ wear-resistant layers, even though the latter have a porosity between 20% and 50%.

[0117] Figure 14The results of micro-scratch tests are shown. These tests involve pressing a Rockwell indenter into the material, with the indenter's movement speed and the applied pressure controlled. This test allows determination of the material's mechanical behavior under pseudo-dynamic conditions at low loading rates and highlights tribological phenomena such as spalling, cracking, and even surface plasticity.

[0118] Therefore, these tests were conducted under gradual loads from 0 to 120 N over a 10 mm range. The four wear-resistant layers tested were derived from powder compositions combining yttrium oxide-stabilized zirconia nanoparticles and LaPO4 filler treated at 800 °C: in the first sample, the LaPO4 content was zero; in the second sample, the LaPO4 content was 25 vol%; in the third sample, the LaPO4 content was 50 vol%; and in the fourth sample, the LaPO4 content was 75 vol%. In each sample, the initiation point of crack 51 and the starting point of spalling 52 were identified.

[0119] Therefore, with increasing filler content, a decrease in the critical loads for cracking and spalling was observed, confirming the LaPO4 dislocation agent effect. In particular, with the addition of 25% by volume of LaPO4, the critical load for cracking decreased from 66 N to 54 N, while the critical load for spalling decreased from 78 N to 63 N.

[0120] Figure 15 The microstructure of a second example of a wear-resistant layer obtained using the method according to this disclosure is shown. In this second example, the powder composition comprises 75 vol% level of yttrium oxide-stabilized zirconium oxide fiber particles and 25 vol% level of LaPO4 particles. The LaPO4 particles had previously undergone a heat treatment step at 1000°C for 120 minutes. The powder composition was mixed by dry mixing for 120 minutes at a mixing ratio Rm of 1:1.

[0121] Sintering is performed via spark plasma sintering, with a compressive pressure P. c The pressure is 100 MPa, and the sintering temperature is T. f The temperature was 1150℃, and the duration was 10 minutes.

[0122] Figures 16A to 16D The test results are then shown, which highlight the contribution of inorganic fillers in the YSZ fiber matrix to achieve a wear-resistant layer with reduced porosity and thus greater resistance to corrosion.

[0123] Four samples were tested on a wear resistance test bench consisting of three blades fixed on a test disc: the position and speed of the test disc relative to the sample were controlled to apply a blade rotation speed of 210 m / s, a penetration speed of 15 μm / s into the wear-resistant material, and a penetration distance of 250 μm.

[0124] therefore, Figures 16A to 16D This is a photo of the marks left by the test blade in the wear-resistant layer of the sample.

[0125] The first sample (its traces are in) Figure 16A (As can be seen in the image) was obtained from a powder composition containing only yttrium oxide-stabilized zirconia fiber particles. Sintering was performed by spark plasma sintering at a compressive pressure P. c The pressure is 100 MPa, and the sintering temperature is T. f The temperature was set at 1100℃ for 5 minutes, resulting in a porosity of 34%. Cracks were observed in the contact area, indicating poor wear resistance of the sample.

[0126] exist Figure 16B The second sample, from which traces can be seen, was obtained from a powder composition combining yttrium-stabilized zirconia fiber particles and 25% by volume of LaPO4 filler treated at 800°C. This powder composition was dry-mixed at a mixing ratio Rm of 0:1. Sintering was performed by spark plasma sintering under a compression pressure P. c The pressure is 100 MPa, and the sintering temperature is T. f The temperature was set at 1050℃ for 5 minutes, resulting in a porosity of 32%. No contact zone cracking was observed, indicating wear resistance; however, metal transfer was noted. At the end of the test, the wear rate of the test blade was measured to be 16.8%.

[0127] exist Figure 16C The third sample, from which traces can be seen, was obtained from a powder composition combining yttrium-stabilized zirconia fiber particles and 25% by volume of LaPO4 filler treated at 1000°C. This powder composition was dry-mixed at a 1:1 mixing ratio Rm. Sintering was performed by spark plasma sintering under a compression pressure P. c The pressure is 100 MPa, and the sintering temperature is T. f The temperature was set at 1050℃ for 5 minutes, resulting in a porosity of 30%. No contact zone cracking was observed; metal transfer was also significantly reduced, demonstrating excellent wear resistance. After the test, the wear rate of the test blade was measured to be 7.2%.

[0128] exist Figure 16D The fourth sample, from which traces can be seen, was obtained from a powder composition combining yttrium-stabilized zirconia fiber particles and 25% by volume of LaPO4 filler treated at 1000°C. This powder composition was dry-mixed at a 1:1 mixing ratio Rm. Sintering was performed by spark plasma sintering under a compression pressure P. c The pressure is 100 MPa, and the sintering temperature is T. fThe temperature was set at 1100℃ for 5 minutes, resulting in a porosity of 23%. Contact zone cracking was observed, leading to poor wear resistance in the sample.

[0129] Figures 17 to 1 Figure 9 shows the results of another test, highlighting the contribution of the heat pretreatment temperature. In this test, two samples were prepared: both samples were obtained from a powder composition that combined yttrium-stabilized zirconia fiber particles with 25% by volume level LaPO4 filler.

[0130] In both cases, the LaPO4 filler underwent heat treatment: in the first case, the heat treatment was carried out at 900°C; in the second case, the heat treatment was carried out at 1100°C.

[0131] Figure 17 The densification curves 61 for the matrix, 62 for the inorganic filler treated at 900°C, and 63 for the inorganic filler treated at 1100°C are shown under SPS production conditions as a function of sintering temperature. It can be seen that curve 63 is closer to curve 61 than curve 62; therefore, the matrix 64 and the LaPO4 filler 65 are actually solidified simultaneously, and thus solidified in a more uniform manner during sintering.

[0132] Figure 18A and 18B The microstructure of each sample after undergoing the same SPS sintering step at 1050 °C and 100 MPa is shown. Therefore, relative to the first sample... Figure 18A Neutralization relative to the second sample Figure 18B It is noted that LaPO4 filler 65 has a very different microstructure in terms of particle size, which affects the consolidation parameters between matrix 64 and filler 65.

[0133] Figure 19A and 19B This shows the wear resistance behavior of the two samples under the same test parameters. Therefore, from Figure 19A As can be seen, the sample treated with filler at 900℃ exhibited numerous fractures in the traces, indicating poor wear resistance. In contrast, at... Figure 19B The sample treated with the filler at 1100℃ exhibited ideal wear resistance, with no breakage or migration.

[0134] Although the invention has been described with reference to specific exemplary embodiments, it will be apparent that modifications and changes can be made to these examples without departing from the general scope of the invention as defined by the claims. In particular, various features of the different embodiments shown or mentioned may be combined in other embodiments. Therefore, the specification and drawings should be considered illustrative rather than restrictive.

[0135] It is equally obvious that all features described with reference to a method can be transposed individually or in combination to a device, and conversely, all features described with reference to a device can be transposed individually or in combination to a method.

Claims

1. A method for manufacturing a wear-resistant layer (12), comprising the following steps: The inorganic filler with a layered crystal structure is pretreated by heat, and at the end of the heat pretreatment step, at least 80% by volume of the inorganic filler is in the dehydrated phase. A powder composition (30) comprising at least ceramic particles and the inorganic filler is prepared, wherein the inorganic filler comprises 1% to 75% by volume in the powder composition, the inorganic filler is LaPO4, and the ceramic particles are yttrium oxide-stabilized zirconia particles. Compress the powder composition (30), and The compressed powder composition (30) is sintered to obtain a wear-resistant layer (12). The heat pretreatment step is performed at 1100°C for 30-120 minutes. During the sintering step, the powder composition is subjected to a uniaxial pressure between 25 and 100 MPa. During the sintering step, the applied temperature is between 900°C and 1200°C. The duration of the sintering step is between 1 and 30 minutes, and The pressure, temperature, and duration of sintering applied during the process are selected to obtain a volumetric porosity of the wear-resistant layer between 0.1% and 50%.

2. The method of claim 1, wherein at least 50% of the ceramic particles have a shape factor greater than or equal to 3, the shape factor corresponding to the ratio [maximum particle size] / [maximum lateral particle size].

3. The method of claim 1, wherein at least 50% of the ceramic particles have a shape factor less than or equal to 1.5, the shape factor corresponding to the ratio [maximum particle size] / [maximum lateral particle size].

4. The method according to claim 1, wherein the microhardness of the inorganic filler is less than the microhardness of the ceramic particles, wherein the Young's modulus of the inorganic filler is less than the Young's modulus of the ceramic particles, and wherein the toughness of the inorganic filler is less than the toughness of the ceramic particles.

5. The method according to claim 1, wherein at least 95% by volume of the inorganic packing is in the dehydration phase.

6. The method according to claim 1, wherein the inorganic filler in the powder composition (30) contains between 10% and 50% by volume.

7. The method of claim 1, comprising the step of mixing the powder composition (30), wherein the mixing step is performed by dry mixing, wherein the three-dimensional dynamic mixer comprises mixing beads in a mass ratio of 0:1 to 1:1 relative to the powder composition, and wherein the duration of the mixing step is from 5 minutes to 4 hours.

8. The method according to claim 1, wherein the sintering step is performed by discharge plasma sintering.

9. A method for manufacturing a substrate (10) coated with a wear-resistant layer (12), the substrate (10) being a turbine engine component, wherein the wear-resistant layer is formed on the substrate by performing the method according to any one of claims 1 to 8, and a powder composition (30) is deposited on the surface (S) of the substrate (10).

10. A method for manufacturing a substrate (10) coated with a wear-resistant layer (12), said substrate being a turbine engine component, comprising the following steps: The wear-resistant layer is manufactured by implementing the method according to any one of claims 1 to 9. The wear-resistant layer thus manufactured is deposited on the surface (S) of the substrate, and The wear-resistant layer thus deposited is bonded to the surface of the substrate.

Citation Information

Patent Citations

  • ABRADABLE VARIABLE DENSITY coating

    FR3044945A1

  • METHOD FOR MANUFACTURING AN ABRADABLE LAYER

    FR3082765A1

  • Turbine ring assembly

    US20120027572A1

  • Nano complex phase thermal carrier coating material La2Zr2O7-YSZ (Yttria Stabilized Zirconia) prepared by in-situ reaction and preparation method thereof

    CN102060551A

  • Method for manufacturing an abradable layer

    CN112334601A